1988
DOI: 10.1212/wnl.38.11.1705
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic and electric fields agree with intracranial localizations of somatosensory cortex

Abstract: We measured the magnetoencephalogram (MEG), electroencephalogram (EEG), and electrocorticogram (ECoG) after stimulation of contralateral median nerve in four patients with partial epilepsy evaluated for surgery. Quantitative localization estimates from equivalent source modeling were compared with locations of central fissure in hand sensorimotor area determined by cortical stimulations, intraoperative photographs, and examination after excision in frontal lobe. We also measured MEG and EEG in nine control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(64 citation statements)
references
References 0 publications
4
60
0
Order By: Relevance
“…This study demonstrates that MEG recordings modeled as a single ECD can map the primary somatosensory region with high spatial resolution and that the number of distinguishable somatosensory sites is substantially greater than has been previously reported for humans (6,(10)(11)(12)(13)(14)(15)(16)(17)(18). Closely spaced tactile sites on the skin surface can map to distinguishable separate cortical areas on the MRI overlays by using a single FIG.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This study demonstrates that MEG recordings modeled as a single ECD can map the primary somatosensory region with high spatial resolution and that the number of distinguishable somatosensory sites is substantially greater than has been previously reported for humans (6,(10)(11)(12)(13)(14)(15)(16)(17)(18). Closely spaced tactile sites on the skin surface can map to distinguishable separate cortical areas on the MRI overlays by using a single FIG.…”
Section: Discussionmentioning
confidence: 65%
“…However, a variety of neuroimaging tools have been developed which may noninvasively study human mental functions. The human somatosensory cortex has been partially mapped using positron emission tomography (PET) (6), electroencephalography (EEG) (7-9), and magnetoencephalography (MEG) (10)(11)(12)(13)(14)(15)(16)(17)(18) METHODS Somatosensory stimulus-evoked magnetic brain activity generated by the left and right cortex in two neurologically normal undergraduate male subjects was recorded inside of a magnetically shielded room by using a Magnes 37-channel biomagnetometer (Biomagnetic Technologies, San Diego). The neuromagnetic field pattern was recorded over a 144-mm-diameter circular area above the parietotemporal cortex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,18,26,29,33,37,50,55 The authors of several studies on mapping the sensorimotor cortex have reported that despite having a common general organization, variations in the somatotopy are frequently found. 2,6,7,18,26,29,33,37,38,52,53,55 They suggest that Penfield's homunculus be used as a simplified teaching tool but not as an accurate map (Fig. 9).…”
Section: Neural Featuresmentioning
confidence: 99%
“…9). 2,18,38,52,53 Two groups have reported sensorimotor function outside the central lobe. 5,55 These studies suggested that the primary motor cortex may extend beyond the anterior edge of the precentral gyrus.…”
Section: Neural Featuresmentioning
confidence: 99%